Senna occidentalis Link. (Caesalpiniaceae) imbibition curves for NaCl osmotic potential levels up to 0.6 MPa - Delachiave, Maria E. A.; Pinho, Sheila Z. (Fundacion Romulo Raggio, 2002)
An investigation is reported on the statistical model of imbibition curves of the seeds of Senna occidentalis Link. (Caesalpiniaceae), up to Phase II (start of root emission) in osmotic potential levels (0; -0.2; -0.4 and -0.6 MPa), induced NaCl or PEG 6000. The statistical model for both solutions was y = a [1 b exp(-cx)] where y is the fresh matter of seed in g, and x the time of evaluation in h. The analysis of variance of the estimated parameters, showed that with the NaCl solution, the -0.4 and -0.6 MPa levels differed significantly from the 0 and -0.2 MPa levels, and that with the PEG solution, the -0.6 MPa differed from the rest. Prolongation of Phase II occurred as the potential decreased, with both solutions. More reduction in water uptake and prolongation of this phase occurred with the PEG treatment.